ON SOUTHERN ANATOLIAN DOLICHOPODA BOLIVAR, 1880 WITH TAXONOMIC NOTES ON THE GENUS HELLERINA GALVAGNI, 2006 (ORTHOPTERA, RHAPHIDOPHORIDAE) - Rampini, Mauro; Di Russo, Claudio (Fragmenta entomologica, 2008)
In this paper a new synonymy Hellerina Galvagni, 2006 = Dolichopoda Bolivar, 1880 and a new combination Hellerina lycia Galvagni, 2006 = Dolichopoda lycia (Galvagni, 2006). A redescription of male morphology and female description are reported. The affinity with the other Anatolian Dolichopoda and with some species of the sub genus Petrochilosina Boudou-Saltet, 1980, characterized by a bifurcated epiphallus, are discussed.